Procalcitonin and C-reactive Protein for Early Detection of Ventilator Associated Pneumonia in Intubated and Mechanically Ventilated Patients - Yadav, Rajesh; Singh Thapa, Ajay; Shah, Rakesh; Upadhyay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Ventilator associated pneumonia has very high mortality. Inadequate antimicrobial treatment is an import determinant of mortality in ventilator associated mortality. Antimicrobial treatment is usually guided by culture and sensitivity which requires at least 12 to 48 hours. In many recent studies Procalcitonin and C-reactive protein, alone or in combination, has shown a promising predictive ability to detect sepsis. The aim of this study is to find the ability of procalcitonin and C-reactive protein to predict ventilator associated pneumonia. Methods All the mechanically ventilated patients were included except patients with AIDS, neutropenia and if the patient had procalcitonin level more than 0.6 ng/ml. All the patient had procalcitonin and C-reactive protein done daily from the day of intubation till seventh day of intubation. Broncho-alveolar aspirate sample was sent on third day of intubation. Statistical analysis was done to find sensitivity and specificity of both the biomarkers to predict ventilator-associated pneumonia. Results C-reactive protein was high initially and decreased gradually over seven days. Procalcitonin was low and undetectable initially, highest on the third day of intubation and gradually deceased over the next following days. On the third day, Procalcitonin was found to be highly sensitive and specific to detect ventilator associated pneumonia compared to C-reactive protein. Conclusions Compared to C-reactive protein, procalcitonin is a good biomarkers for predicting early pneumonia in intubated and ventilated patients in ICU that can guide us in escalating antibiotics before the availability of culture and sensitivity